1989
DOI: 10.1080/02701367.1989.10607442
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Previous Athleticism on Exercise Habits, Physical Fitness, and Coronary Heart Disease Risk Factors in Middle-Aged Men

Abstract: A longitudinal study was performed to determine differences in physiologic variables, health behaviors, risk factors, or clinical status between former athletes (FA) (N = 345) and nonathletes (NA) (N = 75). The subjects, 420 self-referred white males aged 25-60 years old, were examined for prior athleticism and health. Athleticism was determined through self-reported high school or college athletic history. Baseline physiologic and health behavior characteristics were not different between the two groups. Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
2

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 9 publications
0
12
0
2
Order By: Relevance
“…However, researchers, by gathering a plethora of data from exercise psychology (e.g., adherence data) continue to demonstrate that knowledge, beliefs, and attitudes regarding the role and importance of physical activity do not necessarily equal involvement in it. Although the literature examining former competitive athletes' lifelong health and involvement in physical activity is lacking, several studies point to a neutral, negative, or mixed effect (Brill, Burkhalter, Kohl, & Blair, 1989;King et al, 1992;Montoye et al, 1956;Polednak, 1972;Polednak, 1979). Initial research conducted on former Harvard oarsmen (Dublin, 1932;Rook, 1954) found that the mean age at death was almost identical to that of their classmates.…”
Section: Illuminating the Problemmentioning
confidence: 96%
“…However, researchers, by gathering a plethora of data from exercise psychology (e.g., adherence data) continue to demonstrate that knowledge, beliefs, and attitudes regarding the role and importance of physical activity do not necessarily equal involvement in it. Although the literature examining former competitive athletes' lifelong health and involvement in physical activity is lacking, several studies point to a neutral, negative, or mixed effect (Brill, Burkhalter, Kohl, & Blair, 1989;King et al, 1992;Montoye et al, 1956;Polednak, 1972;Polednak, 1979). Initial research conducted on former Harvard oarsmen (Dublin, 1932;Rook, 1954) found that the mean age at death was almost identical to that of their classmates.…”
Section: Illuminating the Problemmentioning
confidence: 96%
“…Unfortunately, according to Rink (2006) there is little validity to the notion that "if you teach them skills, they will be active. " Brill, Burkhalter, Kohl, Blair, and Goodyear (1989) contradicted this logic in a study that showed that former athletes-the most highly skilled amongst us-are as susceptible to coronary heart disease as the nonathlete. Further, Shephard and Trudeau (2000), in reviewing every longitudinal study conducted in the past 30 years, found virtually no link between PE-type interventions and their curricula on one hand and adult activity patterns on the other.…”
Section: Current Realities Of Physical Educationmentioning
confidence: 84%
“…Significantly, this study used the same leisure-time physical activity questionnaire used in the Tecumseh Community Health Study and the Multiple Risk Factor Intervention Trial studies, contributing to important comparable data using the same instrument and setting the stage for standardization of physical activity assessment. Brill et al (1989) from the Institute of Aerobics Research published another early study. The longitudinal study examined the impact of prior athleticism on specific health outcomes and behaviors.…”
Section: Epidemiologymentioning
confidence: 97%
“…In the 1980s and the 1990s, there was a societal shift in the study of physical activity toward understanding the relationship between physical activity and public health. Articles published in RQES included epidemiological studies about leisure physical activity and job performance (Blair et al, 1980), historical physical activity and orthopedic injuries (Macera et al, 1989), physical activity, fitness, and coronary heart disease (Brill, Burkhalter, Kohl, & Blair, 1989;Rimmer & Looney, 1997;Rohm Young & Steinhardt, 1993), the effects of exercise and brain function (Spirduso, 1983), stress reduction (Berger & Owen, 1988), aging (Fiatarone, 1996), appetite and obesity (Wilmore, 1983), and youth fitness and health (Freedson & Evenson, 1991;Taylor & Baranowski, 1991). Articles were published that studied correlates of physical activity behaviors in youth (Hovell, Hofstetter, Sallis, Rauh, & Barrington, 1992;Pate et al, 1997) and the development of a leisure behavior index (Yu & Mendell, 1980).…”
mentioning
confidence: 99%